Immunochemical properties of some monoclonal IgE antibodies to 4-hydroxy-3-nitrophenylacetyl (NP). - Bose, R (1984)
Several hybridoma cell lines secreting NP-specific, murine IgE antibodies were generated by fusion of P3-X20 (gamma, kappa) tumour cells with spleen cells from (BALB/c X C57B1/6)F1 (CB6F1) mice previously immunized with NP-ovalbumin. Four subclones (designated NP-epsilon-3.57, NP-epsilon-15.88, NP-epsilon-91.58 and NP-epsilon-95.31) were propagated in vivo and milligram quantities of the corresponding IgE antibodies were purified from ascitic fluid by gel filtration, ion exchange chromatography and affinity chromatography. Immunological analyses and sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) indicated that NP-epsilon-15.88, NP-epsilon-91.58 and NP-epsilon-95.31 all possessed lambda 1 (or possibly lambda 3) light chains; and that NP-epsilon-3.57 possessed lambda 2 light chains; NP-epsilon-95.31 also expressed the P3-X20 derived, MOPC-21 kappa light chain. Radioallergosorbent test (RAST) titration curves, generated from the interaction of the four monoclonal IgE antibodies with NP-BSA attached to paper discs (NP-BSA-P) were found to be non-overlapping. Measurements of the relative amounts of NP-epsilon-aminocaproic acid (NP-CAP) and 4-hydro-3-iodo-5-nitrophenylacetyl-epsilon-aminocaproic acid (NIP-CAP) that were required to inhibit by 50% the binding of the 4 IgE antibodies to NP-BSA-P indicated that these antibodies were all heteroclitic, since their affinity for NIP appeared to be higher than their affinity for NP. These results, in conjunction with other findings reported in the literature, suggested that the V regions of NP-specific IgE antibodies are similar to the V regions of NP-specific IgM and IgG antibodies, produced by the same mouse strains. Finally, in vitro histamine release measurements demonstrated that two of these monoclonal IgE antibodies could mediate antigen induced histamine release from passively sensitized rat peritoneal mast cells.